Development of mint (Mentha piperita L.) grown on biosolids: evaluation of productivity and essential oil content - Scavroni, Joseane [UNESP]; Ferreira, Leonardo Cesar [UNESP]; Valmorbida, Janice [UNESP]; Boaro, Carmen Sílvia Fernandes [UNESP] (Brazilian Archives of Biology and Technology, 2009)
Níveis de biossólido equivalentes a 0, 28, 56 e 112 t ha-1 foram avaliados no desenvolvimento de Mentha piperita L. Determinaram-se área foliar e matéria seca total e dos diferentes órgãos, os índices fisiológicos razão de área foliar, área foliar específica, taxa assimilatória líquida e taxa de crescimento relativo, aos 30, 44, 58, 72 e 86 dias após plantio (DAP) e o rendimento de óleo essencial aos 90, 110 e 120 DAP. Os índices fisiológicos revelaram que o biossólido prolongou a fase vegetativa das plantas, que se adaptaram com o tempo e apresentaram comportamentos inversos em relação à produtividade, resultado de seu metabolismo primário e representada pela produção de matéria seca da parte aérea e produção de óleo, resultado do metabolismo secundário. A referida adaptação das plantas de menta à presença do biossólido pode ser devido à função fitorremediadora dessa espécie, cujos mecanismos intrínsecos poderão ser melhor compreendidos na avaliação dos efeitos residuais em sua parte aérea.

Development of Mentha piperita L . on biosolids amended soil with levels equivalent to 0, 28, 56 and 112 t ha-1 was evaluated. In order to measure the productivity and its relation with mint essential oil yield, different indices were determined: leaf area, total and several organ dry matter, leaf area ratio, specific leaf area, net assimilation rate and relative growth rate at 30, 44, 58, 72 and 86 days after planting (DAP), and essential oil yield at 90, 110 and 120 DAP. Physiological indices revealed that biosolids prolonged the vegetative phase of the plants, which adapted themselves to the presence of biosolids with time. Plants showed inverse behaviors in relation to productivity, resulting from the primary metabolism, represented by the shoot dry matter yield, and oil yield, resulting from the secondary metabolism. Adaptation of the mint plants to the growth on biosolids could be due to a phytoremediation function of this species. The intrinsic mechanisms of these processes could be better understood in a further evaluation of residual effects in mint plant shoots.
Keywords: Growth analysis; peppermint; essential oil; sewage-sludge; leaf area; dry matter